Does an austere Europe have a future? - O'Sullivan, Michael (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2017)
The Eurozone crisis is a profoundly structural one in that it has unmasked the inappropriateness of the monetary union for certain member states and the complacency of its governing class. The aims and raison d'être of the European project must now be rethought in an original way and communicated in a clear way to its bewildered citizens. It needs new and reformed institutions, and above ail it needs leaders. Specifically, in the economic arena, policymakers need to broaden the range of policy options to actively consider debt restructurings and the exit of some countries from the Eurozone.